A escola de educação básica na modalidade educação especial no contexto da política de educação especial do estado do Paraná - Piaia, Tiarles Mirlei (2016)
This research aims to understand the trajectory of implementation of the School of Basic Education in Special Education Mode in the context of special education policy of the State of Paraná, Brazil. To achieve this purpose, we proceed with a documental and bibliographic research. The bibliographic references subsidize the analysis of official documents in order to understand the historical and political context of the creation of such documents. To support this analysis, we relied on the Cultural Historical theory, especially in Vygotsky's studies of Special Education, which are in the collection Fundamentos da Defectologia (Fundamentals of Defectology) - Tomo V (1997). In SEED \ DEEIN, we collect data relating to such school implementation process in the municipalities of the state, which we have explored in the light of Bardin's content analysis technique (2011). We identified in this study that the implementation of the School of Basic Education in the Modality Special Education in Paraná State was given by divergences in the orientation of PNEEPEI (BRAZIL, 2008) and of the Decree No. 6571 \ 08 about the enrollment of all students in regular classes as well as the funding to schools by FUNDEB resources be linked to the same condition. Considering the above, was given, in this State, the creation of the Basic Education School in the Special Education Modality by work undertaken by FEAPAES \ PR, with the consent of SEED \ DEEIN and approval of the EEC. In addition to changes in the Special Education Schools designation for Basic Education Schools in Special Education Modality the Paraná State legislation assured this integration to the State System of Education offering schooling and ensuring certification to the students. But after three years of implementation, the proposal required a readjustment by the fact that students could not master the planned curriculum content, which would announce, at the end of 2014, large percentages of failure. Occurred then, in 2014, the administrative and pedagogical organization whose main feature was the adjustment in the student time spent in elementary school in a ten-year cycle. There is, then, that schooling and certification warranty are challenges still to be achieved because the pedagogical responses regarding the appropriation of academic content by the students has not given as efficiently as was the implementation of such school.